Generating local wisdom through the prototype of docudrama “Becak Stasiun” as an educational program on RCTV - Heriyawati, Yanti; Wita, Afri; Mulyadi, Yadi (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
Docudrama is a television program that offers a hybrid genre between reality and fiction to convey the socio-cultural reality of Ciayumajakuning in the form of drama. The purpose of this study is to describe the structure of drama, visualization, and audio of the docudrama prototype, and to support the study of the trial results through appreciation. The method used is descriptive analysis applied to the docudrama prototype. The prototype public test was conducted through a questionnaire to analyze audience appreciation. The title Becak Stasiun represents the Ciayumajakuning community (Cirebon, Indramayu, Majalengka, and Kuningan) is a drama performance set in a train station, Nasi Jamblang, and a fishing village with the Cirebon landscape that supports its visualization. The language used is a mixture of Javanese and Sundanese dialects, accompanied by music and regional songs with a tarling nuance. The results of this study indicate that the audience appreciation survey shows that the Becak Stasiun Dokudrama is entertaining and educational by highlighting the potential of Cirebon, including its artistic and cultural values. As a television show, the prototype of the Docudrama Becak Stasiun represents the ethnography of the Ciayumajakuning community and functions as a medium for conveying local wisdom that attracts the interest of the people of Cirebon and its surroundings.